Modification of wheat gluten for improvement of binding capacity with keratin in hair. Issue 2 (7th February 2018) - Wang, Shukun; Meng, Danyang; Wang, Sisi; Zhang, Zhong; Yang, Ruijin; Zhao, Wei
Abstract : In this study, enzymatic hydrolysis and cationization with epoxypropyldodecyldimethylammonium chloride of wheat protein, an economic protein complex containing great amount of disulfide bonds, were conducted to improve properties such as solubility and disassociation behaviour for recovery of damaged hair when used in shampoo. The optimal conditions for enzymatic hydrolysis were pH 8.2, 55°C with Alcalase for 60 min. After the selected hydrolysis, the degree of hydrolysis, nitrogen solubility index, foaming capacity index, foam stability index, emulsifying activity index and emulsion stability index of hydrolysate with 58.71% of short-chain peptides (less than 1000 Da) were 8.81%, 39.07%, 225%, 56.67%, 9.62 m 2  g −1 and 49.08, respectively. The cationization was followed to raise the isoelectric point of wheat protein hydrolysate from 7.0 to 10.0, which could facilitate the quaternized protein hydrolysate to adhere to the surface of hair at the range of pH 5–6 of hair care products to form more disulfide bonds. The results show that a shampoo with quaternized wheat proteins hydrolysate possesses excellent properties in recovering damaged hair, making the surface of hair smooth and compact.